Radiation imaging using an integrated Radiation Imaging System based on a compact Compton camera under unit 1/2 exhaust stack of Fukushima Daiichi Nuclear Power Station - Sato, Yuki; Terasaka, Yuta (Journal of nuclear science and technology, 2022)
The Fukushima Daiichi Nuclear Power Station (FDNPS) went into meltdown after being hit by a large tsunami caused by the Great East Japan Earthquake on 11 March 2011. Measuring and understanding the distribution of radioactive contamination inside the FDNPS is essential for decommissioning work, reducing exposure to workers, and ensuring decontamination. This paper reports the visualization tests of radioactive contamination in the Unit 1/2 exhaust stack of the FDNPS using a compact Compton camera. Fixed-point measurements were conducted using only a Compton camera and moving measurements using an integrated radiation imaging system (iRIS) that combines a Compton camera with a simultaneous localization and mapping device. For the moving measurements, an operator carrying the iRIS acquires data continuously while walking in a passage near the stack. With both types of measurements, high-intensity contamination was detected at the base of the stack, and detailed three-dimensional (3D) visualization of the contamination was obtained from the moving measurement. The fixed-point measurements estimated the source intensity of the contamination from the reconstructed contamination image acquired by the Compton camera. Furthermore, workers can experience the work environment before actual work by importing a 3D structure model into a virtual reality system displaying the contamination image.